2016
DOI: 10.1088/0963-0252/25/1/015018
|View full text |Cite
|
Sign up to set email alerts
|

The plasma sheath around planar probes: effects of ion collisions

Abstract: The 2D numerical model of the ion current collection by a planar probe has been developed on the basis of a particle in cell with the Monte Carlo collision method for ion motion. This model is used to reveal the effects of ion collisions on the probe sheath area and spatial distribution of plasma density and to warn against current-voltage probe characteristic misinterpretation at plasma density measurements by commonly used Langmuir probe methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…This ratio characterizes the plasma density profile [67]. It was obtained in [68] by the flat probe measurements and the 2D PICMCC simulations [69] that in the absence of ionization in sheaths k-value depends on a gas pressure and is almost independent of a plasma density. For Ar plasma k-value changes with pressure from ∼0.55 for collisionless plasma to ∼0.15 at 200 mTorr [68].…”
Section: Resultsmentioning
confidence: 91%
“…This ratio characterizes the plasma density profile [67]. It was obtained in [68] by the flat probe measurements and the 2D PICMCC simulations [69] that in the absence of ionization in sheaths k-value depends on a gas pressure and is almost independent of a plasma density. For Ar plasma k-value changes with pressure from ∼0.55 for collisionless plasma to ∼0.15 at 200 mTorr [68].…”
Section: Resultsmentioning
confidence: 91%
“…In the previous simulation of the sheath near a planar probe [34], it was discovered that both the effective ion collection area A s and k-value decreased with the pressure increase. It was shown that for each of the given plasma density n 0 and probe potential V pr values the A s value decreased in a similar way as its value in the collisionless case A s 0 [33].…”
Section: Numerical Model: Pic MCC Simulationmentioning
confidence: 97%
“…The 2D numerical model of ion current collection by a planar probe (electrode) [34] is used. A detailed description of the model can be found in [34]. The main model assumptions are as follows.…”
Section: Numerical Model: Pic MCC Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, requires "real-time" feedback through sensors that provide information about the process and thus make the process control truly precise. the cylindrical probe [12] and the flat probe [13], and with simplified numerical approaches for these probes [14]. The relation between ion flux and plasma density in a df rf CCP discharge in various gases has been investigated both experimentally and using the 2D PIC MCC simulation in [15] to obtain the pressure dependence of this relation.…”
Section: Introductionmentioning
confidence: 99%